Al-Ta’āys Al-‘Ilmī Bayn Al-‘Ilm Al-Ḥadīth Wa al-Khuṭāb Al-Daynī: Dirāsat Fī Sūrat Al-Baqarah Namūdhijān - Abdul Mufid (ILMU USHULUDDIN, 2020)
This study is a step to devising and achieving scientific coexistence, or what we call the endless miracle of the Quran in all fields and at all levels. The Quran is like an ocean, the deeper it becomes, the more you discover its potentials. He who looks at it to discover the laws will find his way. He who navigated to discover its linguistic or graphic secrets will find what he wants. He who reads its stories and histories will have fun and enjoyment.